2012
DOI: 10.1159/000338819
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α Stimulates MMP-2 and MMP-9 Activities in Human Corneal Epithelial Cells via the Activation of FAK/ERK Signaling

Abstract: Aims: Herpes simplex virus type-1-induced herpes simplex keratitis (HSK) is a common immunological cornea disease. While previous studies have addressed the role of tumor necrosis factor (TNF)-α and matrix metalloproteinases (MMPs) in HSK, the mechanistic link between TNF-α and MMPs in the pathogenesis of HSK remains elusive. Methods: We first established a HSK mice model and measured the levels of TNF-α, MMP-2 and MMP-9 in the corneas at different time points by ELISA. Next, we employed cultured human corneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 32 publications
5
25
0
Order By: Relevance
“…Taken together, our current results show that NTP effectively decreases cancer cell invasiveness via the MMP-2/-9/uPA system, which is associated with Akt and ERK signalings. Previous data revealed that the MMP/uPA system is regulated through the PI3K-Akt and/or ERK/p38 signalings [22], [43], [44].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our current results show that NTP effectively decreases cancer cell invasiveness via the MMP-2/-9/uPA system, which is associated with Akt and ERK signalings. Previous data revealed that the MMP/uPA system is regulated through the PI3K-Akt and/or ERK/p38 signalings [22], [43], [44].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MMPs are synthesized as latent proforms, which need to be activated prior to secretion . At the transcriptional level, nuclear factor‐kappaB (NF‐ κB) and activator protein‐1 (AP‐1) induce MMPs transcription in response to inflammatory cytokines like interleukin 1β (IL1 β) and tumor necrosis factor α (TNFα) .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies had been shown that TNF-␣ mRNA and TNF-␣ protein were up-regulated during the progression of HSV-1-infected eyes [20]. Furthermore TNF-␣ may play a role in HSV-1-induced herpes simplex keratitis by stimulating MMP9 activity via the FAK/ERK pathway [21]. Chen et al in our team found that MMP9 was increased in HSV-1 induced facial paralysis [18].…”
Section: Discussionmentioning
confidence: 71%